Kajian Feminisme Islam dan Nilai Pembelajaran IPS dalam Serial Gadis Kretek - Ainun Wahayuningtiyas; Dany Miftah M. Nur (Yayasan Literasi Sains Indonesia, 2025)
Rapid social and cultural developments have brought great attention to gender issues and the role of women in society. Islamic feminism emerged as an approach that combines religious values ​​with the struggle for women's rights. The Gadis Kretek series is an interesting media to analyze because it presents a story that contains learning values ​​that are relevant to Social Sciences (IPS). This study aims to describe Islamic feminism reflected in the Gadis Kretek series and to examine the existence of values ​​in Social Sciences (IPS) learning contained in the Gadis Kretek series. The type of research used is descriptive with text analysis using a feminist approach according to Shulamit Reinharz. The analysis process adopts an interpretive qualitative approach that emphasizes the socio-cultural and historical context as the background of the text. Data collection in this study was through observation, interviews and documentation. The results of this study are (1) a study of Islamic feminism in the Gadis Kretek series, including gender discrimination, gender equality and women's struggles, and (2) the values ​​of social studies learning in the Gadis Kretek series, namely (a) social inequality, (b) history, (c) social change and cultural dynamics, (d) democratic values ​​and human rights, (e) social responsibility and solidarity, (f) gender roles in economic development, and (g) resolution of social conflicts.